2021
DOI: 10.1111/sltb.12758
|View full text |Cite
|
Sign up to set email alerts
|

Language, culture, gender, and intersectionalities in suicide theory, research, and prevention: Challenges and changes

Abstract: Over the decades suicidology has experienced many challenges and changes.Language, culture, gender, and intersectionalities of experience have been domains of challenge and change. In this article I document my contributions to suicidology's transformation in these domains. These contributions include challenging stigmatizing and biased suicide-language (e.g., expressions like "successful" and "failed" suicide); questioning gender myths of suicidal behaviors (e.g., the myth that women and men are opposites in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 59 publications
1
21
0
1
Order By: Relevance
“…hesitance to disclose personal stigmatising attitudes) as well as less personal stigmatising attitudes among those with own experiences of suicidality. Additionally, in line with suicide scripts theory (Canetto, 2021 ) and previous studies (Stack and Kposowa, 2008 ; Eskin et al ., 2016 ; Phillips and Luth, 2020 ), suicide normalisation was associated with an increased probability to experience current suicidality. Suicide normalisation may therefore reduce the barrier to consider suicide as an option in difficult life situations and should therefore be considered when developing strategies for suicide prevention.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…hesitance to disclose personal stigmatising attitudes) as well as less personal stigmatising attitudes among those with own experiences of suicidality. Additionally, in line with suicide scripts theory (Canetto, 2021 ) and previous studies (Stack and Kposowa, 2008 ; Eskin et al ., 2016 ; Phillips and Luth, 2020 ), suicide normalisation was associated with an increased probability to experience current suicidality. Suicide normalisation may therefore reduce the barrier to consider suicide as an option in difficult life situations and should therefore be considered when developing strategies for suicide prevention.…”
Section: Discussionsupporting
confidence: 88%
“…suicide normalisation) might increase suicide risk. According to suicide-scripts theory (Canetto, 2021 ), suicidal behaviour is most likely when it is socially accepted or even expected for certain persons in certain situations, what at least partially explains elevated suicide rates in certain regions (Pepper, 2017 ) or among certain social groups such as the elderly (Winterrowd et al ., 2017 ), youth (Kleiman, 2015 ) and sexual minorities (Canetto et al ., 2020 ). In line with that, several studies observed increased national suicide rates in countries with more liberal attitudes towards suicide (Stack and Kposowa, 2008 ; Eskin et al ., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…About one out of five male decedents and one out of six female decedents age 45–64 had JFH. This sex difference in JFH-precipitated suicides may reflect cultural expectations related to gender ( Canetto, 2021 ; Canetto & Sakinofsky, 1998 ). Men, especially middle-aged men with family, have been expected to be the primary breadwinner, which may also explain the higher proportion of married individuals among male than female decedents with JFH.…”
Section: Discussionmentioning
confidence: 95%
“…När det gäller livets sista tid förekommer till exempel olika kulturella förståelser av vad som är "normala sätt att dö" (Ågren 2020). Inom suicidforskningen består kulturellt betingade skript dels av strukturerade narrativ om suicidakten (vem som begår suicid, hur och varför), dels av betydelsen som ges suiciden och hur de begripliggörs (Canetto 2021).…”
Section: Osynliggörandet Av Ett Socialt Problemunclassified